Various Malware Handling Technique - Sulianta, Feri (CENTRAL ASIA AND THE CAUCASUS, 2022)
All malicious computer programs are classified as malware or malicous software. Malware has a variety of characteristics with a variety of destructive actions, the handling varies from one type to another.Various categorizations of malware that are commonly known include: computer viruses, worms, trojan horses, spyware, adware, hoaxes, backdoors, scareware, rootkits, etc. And that's not all, various worms, trojans and viruses can be classified into various categories. Apart from the above classification, there is still malware that is categorized as 'unwanted program'.So you can be sure that computers, internet, data and information in them will always get threats from creatures called malware.